2021
DOI: 10.1111/ger.12533
|View full text |Cite
|
Sign up to set email alerts
|

Cost of providing a mobile dental service for dependent older people

Abstract: Background and Objective: Dental care provision in long-term care facilities (LTCFs) is often a problem despite the high demand. LTCF residents would greatly benefit from a concept that provides an onsite dental care. A rational evaluation of the costs to render this service as well as the cost benefits is worth investigating. This study aimed to calculate the costs involved in providing a mobile dental clinic (MDC) service for LTCF residents in Zurich, Switzerland. Materials and Methods:Cost models for set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In fact, longer term, using a model which has a high initial cost in the long-term could be more cost-efficient when weighing up reduced attendances for unscheduled dental care, A&E or FTAs at fixed-site services. 32…”
Section: Mobile Servicesmentioning
confidence: 99%
“…In fact, longer term, using a model which has a high initial cost in the long-term could be more cost-efficient when weighing up reduced attendances for unscheduled dental care, A&E or FTAs at fixed-site services. 32…”
Section: Mobile Servicesmentioning
confidence: 99%
“…In fact, longer term, using a model which has a high initial cost in the long term could be more cost e cient when weighing up reduced attendances for unscheduled dental care, accident and emergency or FTAs at xed site services. Cost-effectiveness of using a MDS for dependent older people in Switzerland found that although there are high set up costs with this model of care, approximately Euros 466,577 (roughly £403,215), return on investment would be expected by 3 years 32 .…”
Section: Mobile Servicesmentioning
confidence: 99%